2005
DOI: 10.1002/aps.30
|View full text |Cite
|
Sign up to set email alerts
|

Using the Rorschach for exploring the concept of transitional space within the political context of the Middle East

Abstract: The paper presents an application of a new Rorschach index, the Reality-Fantasy Scale (RFS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 17 publications
1
33
0
4
Order By: Relevance
“…Operationalizing the Concept of Transitional Space: The RFS The RFS (Tibon et al, 2005) was designed to assess adaptive use, creation, and preservation of potential or transitional space. The scale was intended to differentiate between possible forms of psychopathology that may occur when one pole of the reality-fantasy continuum collapses into the other.…”
Section: Alexithymia and The Rorschach Thematic Imagerymentioning
confidence: 99%
“…Operationalizing the Concept of Transitional Space: The RFS The RFS (Tibon et al, 2005) was designed to assess adaptive use, creation, and preservation of potential or transitional space. The scale was intended to differentiate between possible forms of psychopathology that may occur when one pole of the reality-fantasy continuum collapses into the other.…”
Section: Alexithymia and The Rorschach Thematic Imagerymentioning
confidence: 99%
“…Psychologically healthy participants, as defined by the RFS, would be expected to score on the scale around zero, whereas significantly lower and higher mean RFS scores would be expected in cases of reality collapse and fantasy collapse, respectively. Previous studies that used the scale in samples of both nonpatients and patients confirmed the hypothesized zero RFS-P score in nonpatients and validated the scale as detecting psychotic proneness (Tibon, Handelzalts, & Weinberger, 2002;Tibon et al, 2005). Nonetheless, because the scale is bipolar with either extreme assumed to represent psychopathological adaptation, the use of the mean alone may mask important results, particularly in patients with dissociative behaviors.…”
Section: Please Scroll Down For Articlementioning
confidence: 64%
“…This comment suggests using a new Rorschach index, the Reality-Fantasy Scale (RFS; Tibon, Handelzalts, & Weinberger, 2005). The RFS is similar to the EII-2 in that it is addressed at capturing impaired psychological manifestations by CS variables, but it differs from the theoretical perspective used to define these manifestations.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…Thus, psychodynamic concepts progressively have given rise to a number of measures derived from performance-based methods. The Ego Impairment Index (EII-2; Viglione et al 2003) and the Reality-Fantasy Scale (RFS; Tibon et al 2005), based on the Rorschach Inkblot Method, or the Social Cognition and Object Relations Scale (SCORS; Westen 1991) based on the Thematic Apperception Test (TAT), are some illustrations for these measures. Given these developments, the complaint that empirically validated psychodynamic tools are not used is certainly neither true nor relevant for personality assessment.…”
Section: Towards a Multi-methods Assessment Of Mental Functioningmentioning
confidence: 99%